Penyuluhan Pendidikan Seksualitas dan Gaya Berpacaran Sehat pada Remaja - Purba, Novia Sri Parindu; Sukhita, Yuvati Atthaladdha (Universitas Bunda Mulia, 2023)
There are many cases of pregnancy outside of marriage in adolescents due to lack of parental supervision, lack of knowledge about sex, and the consequences of unhealthy dating styles. This is also related to the stages of adolescent development, which is why there is a need for sex education from an early age. Furthermore, the need for exposure to knowledge about love adolescents to avoid the increasing number of pregnancies at an early age. This service activity aims to educate adolescents about romance, sexuality, and dating styles involving 187 students at SMA Charitas, namely 61 class X participants, 63 class XI participants, and 63 class XII participants. This service uses a psychoeducational approach. The result of this activity is a discussion about the development of adolescents, who are often trapped in free sex or free marriage. This is due to the existence of two influencing factors, external and internal. Internal factors are factors that originate within the teenager himself, such as knowledge, attitude toward sexuality, self-control, lifestyle, social activity, age, and religion/spirituality. External factors originate from outside the adolescent, such as family relationships, social media exposure, values, social culture, and norms that serve as social support for adolescent behavior. Thus, through this activity, participants are expected to acquire knowledge and avoid behaviors that could ruin their lives in the future